MODEL EXPECTATION-CONFIRMATION DALAM MEMAHAMI NIAT KEBERLANJUTAN PENGGUNAAN MOBILE BANKING PADA SEKTOR MICROFINANCE - Ni Kadek Sahitya Badreswari (Jurnal Ilmu Akuntansi, 2025)
Purpose: This study aims to analyze the factors influencing the continued use of mobile banking services at LPD Desa Adat Bualu. It specifically investigates the impact of confirmation, perceived usefulness, and satisfaction on users' continuance intention, using the Expectation-Confirmation Model (ECM) as its theoretical framework. The research addresses the challenge of sustaining mobile banking adoption in microfinance institutions to enhance financial inclusion in rural areas. Methodology/approach: The research used a quantitative confirmatory approach with a census sampling technique, surveying all 178 active mobile banking users at LPD Desa Adat Bualu. Primary data were collected through an online questionnaire using a 5-point Likert scale. The collected data were analyzed using multiple linear regression with SPSS version 25. Results/findings: The findings show that confirmation, perceived usefulness, and satisfaction all have a positive and significant influence on the continuance intention of LPD Desa Adat Bualu's mobile banking users. This is supported by the t-test results, where the significance values for all three variables are less than 0.05. The R-squared value of 86.3% indicates that these three variables collectively explain a substantial portion of the variance in continuance intention. Conclusion: The study concludes that the continued use of mobile banking at LPD Desa Adat Bualu is significantly driven by user confirmation, perceived usefulness, and satisfaction. LPDs and other microfinance institutions should focus on ensuring that their mobile banking services meet or exceed user expectations to foster long-term adoption and contribute to broader financial inclusion.